2014
DOI: 10.5935/paet.v7.n1.05
|View full text |Cite
|
Sign up to set email alerts
|

Tomato production in function of sulfur doses application

Abstract: The importance of sulfur (S) has already been noted by various cultures, especially on production aspects; however it might be a limiting factor of productivity due to intensive cultivation system. The purpose of this study was to evaluate the sulfur application on the tomato productivity development. An experiment was conducted in a greenhouse, on 4 kg vessels of soil, in Guarapuava-PR. The experiment was arranged in entirely randomized blocks, of which 6 doses of S (0, 20, 40, 60, 80 and 100 mg kg-1) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Sulfur serves regulatory and catalytic functions in the plant cells, and it is taken up in its inorganic form as sulfate-SO4 2− [79,80]. Sulfate can be absorbed from the soil and translocated within the plants through the activity of sulfate transporters (SULTRs) in the Due to the foregoing attributes of gypsum, different studies have demonstrated the potential of gypsum and associated S-containing compounds to improve the growth of many crops, including cabbage [71], barley [17], maize [72] and tomato [73] grown under salinity stress conditions (Table 1). Nevertheless, gypsum needs to be applied in large quantities to be highly effective in reclaiming saline soils [56,74].…”
Section: Regulatory Roles Of Sulfur In Plants Under Salinity Stressmentioning
confidence: 99%
“…Sulfur serves regulatory and catalytic functions in the plant cells, and it is taken up in its inorganic form as sulfate-SO4 2− [79,80]. Sulfate can be absorbed from the soil and translocated within the plants through the activity of sulfate transporters (SULTRs) in the Due to the foregoing attributes of gypsum, different studies have demonstrated the potential of gypsum and associated S-containing compounds to improve the growth of many crops, including cabbage [71], barley [17], maize [72] and tomato [73] grown under salinity stress conditions (Table 1). Nevertheless, gypsum needs to be applied in large quantities to be highly effective in reclaiming saline soils [56,74].…”
Section: Regulatory Roles Of Sulfur In Plants Under Salinity Stressmentioning
confidence: 99%
“…The growth of tomatoes is significantly influenced by the presence of sulfur and sulfurcontaining compounds, which serve vital roles as signaling molecules in normal metabolic processes and under stress conditions. A significant study by Silva et al [13] highlighted that sulfur application led to increased tomato yield and fruit production. However, there is a dearth of comprehensive information regarding how sulfur fertilization may affect tomato quality, particularly concerning bioactive compounds and aromatic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…However, both N and S, may present synergism and to some extent influence fruit production, maturation and quality (Marschner, 2012). Within this context, Silva et al (2014) verified that the N/S ratio decreases with application of S in the tomato, also noticing that the balance between N and S is important, because higher rates of one nutrient can lead to less availability of the other to the plants, growth, yield and post-harvest quality of the crop. Due to studies scarcity on sulphate fertilization in tomato, the present work aimed to evaluate the interaction between N and S in tomato fruit quality.…”
Section: Introductionmentioning
confidence: 76%